A model of the overall satisfaction of children escorts using public playgrounds. Issue 4 (2nd October 2022) - Karampetsios, Thomas; Afthinos, Yanni
ABSTRACT: The current study aimed to conceptualize the elements influencing children escorts' overall satisfaction using public playgrounds in Greece. Three hundred and four children escorts ( n = 304), using playgrounds located in the cities of Central Greece, and one on the island of Lesbos, were questioned. The means of data collection was the questionnaire "Children escorts' satisfaction from using public playgrounds" (Zaharioudaki & Afthinos [2014]. Ικανοποίηση των συνοδών των παιδιών που ϵπισκέπτονται τις παιδικές χαρές της Κρήτης [Satisfaction of children escorts who visit public playgrounds in Crete]. In 15th HSASMR Conference (pp. 108–110). HSASMR. https://www.elleda.gr/sites/default/files/15o_synedrio_-_2014_0.pdf ). The data factor analysis resulted in a model of playground service elements influencing children escorts' overall satisfaction, including "safety", "maintenance", "environment stimulating social interaction", "use of the installation", "apparatus" and "accessibility". Furthermore, these identified service elements fitted Tsuji et al. ([2007]. Consumer satisfaction with an action sports event. Sport Marketing Quarterly, 16, 199–208) conceptualization as core and peripheral. Specifically, there was evidence that, for the children escorts to express an overall positive satisfaction attitude toward a public playground, they should first express a positive satisfaction attitude to core service elements such as "maintenance" as well as "apparatus", and secondarily to the other peripheral service elements.